Respostas

A melhor resposta!
2014-01-11T23:31:41-02:00
y = x² - 8x - 9
a = 1               b = - 8                  c = - 9

V = (Xv, Yv)

Xv =   - b   
         2a

Yv = 
Δ  
        4a

Xv = - (- 8)   
        2 . 1
Xv = 8 ÷ 2
Xv = 4

Δ = b² - 4ac
Δ = (- 8)² - 4 . 1 . (- 9)
Δ = 64 + 36
Δ = 100

Yv = - 100  
        4 . 1
Yv = - 100 ÷ 4
Yv = - 25

Resposta: (4; - 25)
1 5 1
2014-01-11T23:33:28-02:00
y=x²-8x-9
-b/2.a => 8/2 = 4
Xv = 4
y = x² - 8x - 9

y = 16 - 32 - 9
-b/2.a => 8/2 = 4

Xv = 4
y = x² - 8x - 9
y = 16 - 32 - 9
V=(4,-25)